Hazard And Risk Control Analysis Using Failure Mode Effect Analysis and Event Tree Analysis Methods (Case Study: PT Indo Transport Abdimas) - Bagus Febriyana; Buang Turasno; Faris Humami; Ethys Pranoto (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
Work accidents in the bus transportation sector remain a critical challenge requiring systematic and data-driven intervention. PT Indo Transport Abdimas recorded 67 traffic accidents and 13 occupational incidents between March 2022 and October 2025, reflecting a broader trend of increasing workplace risks. This study aims to identify hazards, determine risk priorities, and formulate Occupational Health and Safety (K3) control recommendations for office and workshop areas. An integrated approach combining Failure Mode and Effect Analysis (FMEA) and Event Tree Analysis (ETA) was applied. Data were collected through observation, work environment measurements, occupational health examinations, interviews, and probability questionnaires. Across 16 work divisions in four operational areas, 20 failure modes were identified and evaluated using a modified FMEA framework that integrates environmental and health data into Severity (S), Occurrence (O), and Detection (D) parameters. The Risk Priority Number (RPN) results show that the Finished Goods Warehouse division, characterized by unergonomic posture, has the highest risk (RPN 201.20), followed by vehicle security (RPN 199.89) and falling hazards (RPN 146.22). ETA modeling indicates that applying five control layers increases safe condition probability to 91.98%, compared to a 9.300 × 10⁻³ probability of severe accidents without intervention. This study contributes a quantitative multi-source FMEA methodology that reduces reliance on subjective judgment and demonstrates how FMEA outputs inform ETA scenario design. Recommended controls follow ISO 45001:2018 hierarchy, including ergonomic improvements, elimination of manual lifting, installation of wheel chocks, and safety training. Keywords: Failure Mode and Effect Analysis, Event Tree Analysis, Occupational Safety and Health, Risk Priority Number, Bus Transportation